Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/bjd.14885
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase‐activating polypeptide promotes eccrine gland sweat secretion

Abstract: This is the first report demonstrating that PACAP may play a crucial role in sweat secretion via its action on PAC1R located in eccrine sweat glands. The mechanisms underlying the role of PACAP in sweat secretion may provide new therapeutic options to combat sweating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…More recently, we have reported that PACAP gene-deficient mice develop dry eye-like symptoms such as corneal keratinization and tear reduction, and have shown that PACAP eye drops stimulate tear secretion via an adenylyl cyclase/ cyclic adenylyl cyclase monophosphate/protein kinase A (AC/cAMP/PKA) cascade, which in turn stimulates the translocation of aquaporin 5 from the cytosol to the membrane of lacrimal acinar cells to bring about an increase in water permeability [ 3 ]. It has also been demonstrated that injection of PACAP into the footpads of mice significantly promotes sweat secretion at the injection site [ 4 ]. These reports suggest that PACAP could also prove clinically useful for the treatment of dry eye disorder and sweating disorder.…”
Section: Reviewmentioning
confidence: 99%
“…More recently, we have reported that PACAP gene-deficient mice develop dry eye-like symptoms such as corneal keratinization and tear reduction, and have shown that PACAP eye drops stimulate tear secretion via an adenylyl cyclase/ cyclic adenylyl cyclase monophosphate/protein kinase A (AC/cAMP/PKA) cascade, which in turn stimulates the translocation of aquaporin 5 from the cytosol to the membrane of lacrimal acinar cells to bring about an increase in water permeability [ 3 ]. It has also been demonstrated that injection of PACAP into the footpads of mice significantly promotes sweat secretion at the injection site [ 4 ]. These reports suggest that PACAP could also prove clinically useful for the treatment of dry eye disorder and sweating disorder.…”
Section: Reviewmentioning
confidence: 99%
“…PACAP has a widespread occurrence in the body and a broad array of functions (Reglodi and Tamas 2016 ). Among others, PACAP influences gastrointestinal, urinary and cardiovascular functions (Heppner et al 2018 ; Parsons and May 2018 ; Reglodi et al 2018a ), plays a role in reproduction and pregnancy (Lajko et al 2018 ; Reglodi et al 2012 ; Ross et al 2018 ), has diverse behavioral and cognitive functions (Farkas et al 2017 ; Gupta et al 2018 ; Han et al 2014 ; King et al 2017 ), plays roles during both early development and aging (Fulop et al 2018 ; Reglodi et al 2018b ; Watanabe et al 2007 ), as well as influences the functions of both endocrine and exocrine glands (Bardosi et al 2016 ; Egri et al 2016 ; Prevost et al 2013 ; Sasaki et al 2017 ). VIP has also been shown to have diverse actions in addition to the originally described vasodilatory effects (Gozes 2008 ; Hill et al 2007 ; Moody and Gozes 2007 ; Vu et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…report the expression of another neuropeptide, the pituitary adenylate cyclase‐activating polypeptide (PACAP) – a VIP family member – in periglandular nerves, and also find its receptor, PAC1R, in sweat secretory cells of mice and humans. Furthermore, subcutaneous injection of PACAP induced sweat secretion in mice, which was inhibited by an antagonist of PAC1R . Thus, the involvement of the PACAP–PAC1R pathway in sweat secretion is demonstrated.…”
mentioning
confidence: 86%
“…In this issue of the BJD , Sasaki et al . report the expression of another neuropeptide, the pituitary adenylate cyclase‐activating polypeptide (PACAP) – a VIP family member – in periglandular nerves, and also find its receptor, PAC1R, in sweat secretory cells of mice and humans.…”
mentioning
confidence: 99%